Data from: Embryogenesis in the plant parasitic nematode Heterodera glycines is independent of host-derived stimulation - Thapa, Sita; Schroeder, Nathan; Patel, Jayna; Reuter-Carlson, Ursula (University of Illinois at Urbana-Champaign, 2017)
This dataset includes early embryogenesis and post-embryonic development of Soybean cyst nematode.
Keywords: Soybean cyst nematode; Embryogenesis; Post-embryonic development